Determination of Quality Assurance for Maternal and Child Health Services in Baghdad City - Sa’adoun, naji; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2010)
Objective: To determine the quality assurance for maternal and child health care services in Baghdad City. Methodology: A descriptive study is conducted throughout the period of November 28th 2008 to October 10th 2009. A simple random sample of (349) is selected through the use of probability sampling approach. The study sample was divided into four groups which include (220) consumers, (35) medical staff, (72) nursing staff and (22) organization structure (primary health care centers). Data were collected through the use of assessment tools. It was comprised of four questionnaires and overall items included in these questionnaires are (116) items. The study included assessment of organization structure. Data were collected through the utilization of constructed questionnaire and the interview technique as a mean of data collection. Data analysis was performed through the use of descriptive statistical data analysis approach graphical presentation by bar-chart, frequencies, percentages and mean of scores and inferential statistical data analysis approach which is presented as chi-square procedure. Result: The findings and conclusion of the study indicate that there is overload of target population on primary health care centers, poor designed building, statistical program and data reporting system was poor, decrease core financial support and inadequacy of funding for primary health care centers, there is increased demand and decreased supply of primary health care workforce and poor health education for consumers in primary health- care centers.